Cytochrome P450-dependent drug oxidation activities and their expression levels in liver microsomes of chimeric TK-NOG mice with humanized livers. (June 2022) - Uehara, Shotaro; Yoneda, Nao; Higuchi, Yuichiro; Yamazaki, Hiroshi; Suemizu, Hiroshi
Abstract: Hepatic cytochrome P450 (P450)-dependent drug oxidation activity has not been completely characterized in chimeric TK-NOG mice with humanized livers (humanized liver mice). In this study, we examined several drug oxidation activities catalyzed by liver microsomes from humans, humanized liver mice, and TK-NOG mice using 9 P450 substrates. The catalytic activities of liver microsomes from humans and humanized liver mice showed relatively similar rates of oxidation of 7-ethoxyresorufin, coumarin, 7-pentoxyresorufin, flurbiprofen, S -mephenytoin, chlorzoxazone, and midazolam, whereas bufuralol 1′-hydroxylation and propafenone 4′-hydroxylation (rodent-specific propafenone oxidation activity) were higher in humanized liver mice than in humans. In addition, P450 protein expression levels in the humanized mouse liver were quantified using a liquid chromatography–tandem mass spectrometry-based protein quantification method. Quantification of P450 enzymes showed a 3-fold difference between human and humanized liver mouse livers, except for CYP2B6, which showed an approximately 6-fold difference. Overall, most P450-dependent drug oxidation activities were comparable between liver microsomes from human and humanized liver mice based on the similar expression levels of human P450 enzymes. However, some differences were observed between both species, including considerable differences in bufuralol 1′-hydroxylation and propafenone 4′-hydroxylation activities. Graphical abstract: Image 1